Changing trends in the indication of caesarean delivery in multigravida- experience from a referral center in Eastern India: a prospective study - Sebastian, Nikhil; Pradhan, Anup; Lucksom, Pesona Grace (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean delivery is one of the commonly performed surgical procedures in obstetrics in today’s practice. The objective of this study was to estimate the overall incidence and indications of primary caesarean delivery among multiparous women and to study the immediate maternal and perinatal outcome. Methods: It was a prospective observational study done in Sikkim Manipal Institute of Medical Science, Sikkim, India. It included all pregnant women after 28 weeks of gestation who had normal vaginal delivery in previous pregnancy but underwent caesarean delivery during current pregnancy (n=120) from January 2016 to December 2016. Authors collected data using a pro forma. Relevant history including demographic details, relevant clinical, laboratory and radiological examination, indication for caesarean delivery, details of delivery and neonate, and duration of hospital stay were noted. Data was described using descriptive data like mean and percentages. Results: Out of 1646 deliveries conducted, 49% were by caesarean section. It included 7.29% primary caesarean delivery in multigravida. Majority of women (27%) were in the age group 25-29. Maternal request was the commonest indication for caesarean delivery (21.66%). Atonic PPH was the commonest intraoperative complication (2.5%). Surgical site infection was the commonest post-operative morbidity (3.33%). There were 51 perinatal morbidity and 2 perinatal mortality. There was no maternal mortality. Conclusions: Caesarean section rates in this study was higher than WHO recommendation (15% versus 49.69%). This shift in trend can be attributed to higher number of maternal request for caesarean delivery which can be avoided by good analgesic facility and good counselling.